ПРОБЛЕМА ФОРМУВАННЯ У ШКОЛЯРІВ ПІЗНАВАЛЬНОГО ІНТЕРЕСУ ДО МУЗИЧНИХ ЗАНЯТЬ (Педагогіка вищої та середньої школи, 2007)
The article deals with the types of pedagogical skills and habits which help the future teachers to form for is hoolchildren the cognitive interest to music lessons.